Teacher use of the L2 and student attention in a Spanish language classroom: establishing a functional relationship using single-case design - Sponberg, Erica Ruth Marilyn Grace (My University, 2025)
Much debate surrounds the effectiveness of a teacher’s use of a second language (L2) in world language (WL) classrooms. Although teacher educators and language teaching scholars identify the use of an L2 in instructional delivery as a high value skill (Ellis, 2005; Gilsan & Donato, 2017), there is a paucity of research in measuring its effectiveness on student outcomes (Chaudron, 2001; Egber, 2007; Norris & Ortega, 2000; Ortega, 2005; Plonsky & Gass, 2011; Plonsky, 2014). However, student attention to task can be used as an indicator of student success (Logan & Etherton, 2008; Logan, 1988). This study investigates the relationship between a WL teacher's use of the Spanish language and student attention to task in three level-one high school Spanish language classrooms, using a multiple-base line across group design. Results suggest that there is no significant effect on student attention to task regardless of whether the instructor is using the L1 (English) or the L2 (Spanish).
Keywords: Second language acquisition; Single case design; World language teaching; Target language use; Classroom research